Economic development of Bangladesh that occurred through the CSR activities of Chevron Bangladesh - Shahriar, Md. Shafkat (Brac University, 2021)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2020.